1964
DOI: 10.1126/science.144.3624.1346
|View full text |Cite
|
Sign up to set email alerts
|

RNA Synthesis in Rat Seminal Vesicles: Stimulation by Testosterone

Abstract: Within 70 minutes after the administration of testosterone to rats castrated 12 to 15 hours previously, the rate of synthesis of RNA in the seminal vesicle is increased by 50 percent and continues to rise until approximately 50 minutes after injection when a two- to threefold increase was attained. No further increase was detected for as long as 240 minutes after hormone administration. The base composition of the pulse-labeled RNA was intermediate between that of the total seminal vesicle RNA and DNA-like RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1965
1965
1987
1987

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…At this time no changes in the pool size of nucleotides were detected, but at longer times of exposure to the steroid changes do occur (Wicks & Kenney, 1964). This could mean that, in this tissue, the levels of RNA precursors are under androgen control.…”
Section: Transcriptional and Post-transcriptional Aspects Of The Mechmentioning
confidence: 80%
See 1 more Smart Citation
“…At this time no changes in the pool size of nucleotides were detected, but at longer times of exposure to the steroid changes do occur (Wicks & Kenney, 1964). This could mean that, in this tissue, the levels of RNA precursors are under androgen control.…”
Section: Transcriptional and Post-transcriptional Aspects Of The Mechmentioning
confidence: 80%
“…There are several lines of evidence demonstrating the stimulatory effect of androgens on RNA synthesis in various androgen-sensitive tissues, such as rat ventral prostate gland (Liao, 1968;Williams-Ashman & Reddi, 1971 (Wicks & Kenney, 1964;Dubovsky & Kochakian, 1973), mouse kidney (Avdalovic & Kochakian, 1969;Frieden & Ku, 1971;Dubovsky & Kochakian, 1973), flank organ (Giegel, Stolti, Weinstein & Frost, 1971), bone marrow (Minguell et al 1971;Sierralta et al 1974), submaxillary gland (Chrétien, 1972), muscle (Florini, 1970) and chick oviduct (Palmiter & Haines, 1973).…”
Section: Transcriptional and Post-transcriptional Aspects Of The Mechmentioning
confidence: 97%
“…Wicks & Kenny (1964), using radioactively labelled nucleotides, demonstrated a 50°, rise in uptake of radioactivity into seminal vesicle RNA only 70 min after Fig. 9.…”
Section: Discussionmentioning
confidence: 96%
“…Using the in-vivo labelling technique, Wicks & Kenny (1964) observed an increase in the specific activity of RNA in the seminal vesicle of recently castrated rats within 30 min of testosterone administration. Mainwaring & Peterken (1971) reported that androgens induced a rapid and transient increase in incorporation of [3H]uridine into prostatic nuclei of castrated rats.…”
Section: Discussionmentioning
confidence: 96%